2021
DOI: 10.1002/jcb.30022
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐based investigation of MARK4 inhibitory potential of Naringenin for therapeutic management of cancer and neurodegenerative diseases

Abstract: MAP/microtubule affinity-regulating kinase 4 (MARK4) is a member of serine/threonine kinase family and considered an attractive drug target for many diseases. Screening of Indian Medicinal Plants, Phytochemistry, and Therapeutics (IMPPAT) using virtual high-throughput screening coupled with enzyme assay suggested that Naringenin (NAG) could be a potent inhibitor of MARK4. Structure-based molecular docking analysis showed that NAG binds to the critical residues found in the active site pocket of MARK4. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…IC50 is the concentration of ligand/drug required for 50% inhibition [ 24 ], i.e., concentration of the inhibitor (ligand) needed to attain 50% inhibition (binding saturation) of the enzyme (receptor). IC 50 was found to be µM and the value of this order can be correlated with earlier reported MARK4 inhibitors [ 25 , 26 ], thus revealing the fact that Mtf, an antidiabetic drug, inhibits the kinase activity of MARK4. This reinforces the importance of Mtf use in NDs.…”
Section: Resultssupporting
confidence: 81%
“…IC50 is the concentration of ligand/drug required for 50% inhibition [ 24 ], i.e., concentration of the inhibitor (ligand) needed to attain 50% inhibition (binding saturation) of the enzyme (receptor). IC 50 was found to be µM and the value of this order can be correlated with earlier reported MARK4 inhibitors [ 25 , 26 ], thus revealing the fact that Mtf, an antidiabetic drug, inhibits the kinase activity of MARK4. This reinforces the importance of Mtf use in NDs.…”
Section: Resultssupporting
confidence: 81%
“…Investigations have shown that α-amylase inhibition aids in regulating glucose levels [17]. Polyphenols, their derivatives and other naturally derived compounds show therapeutic potential against various diseases such as cancer [18][19][20][21], neurodegenerative disorders [22,23], diabetes [24,25] and many more.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular docking method helps predict a compound's binding orientation within the receptor's binding pocket and its consequent binding affinity (54)(55)(56). Docking of selonsertib with the CDK6 shows a promising score and excellent binding affinity.…”
Section: Molecular Dockingmentioning
confidence: 99%